2018
DOI: 10.1080/13697137.2018.1476133
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and its associated factors in Chinese middle-aged women

Abstract: There was a difference in HRQOL by menopausal stage in middle-aged Chinese women. Menopause might exert a negative impact on HRQOL, adjusting for menopausal symptoms and sociodemographic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Premenopozal dönemdeki kadınların fiziksel fonksiyon skorları, perimenopozal dönemdeki kadınlarınkine göre oldukça yüksektir. 31 Mishra ve Kuh, yaşam kalitesi ile menopozal geçiş, sosyoekonomik faktörler, yaşam biçimi ve stres arasındaki ilişkiyi araştırdıkları çalışmalarında; en az 1 yıldır perimenopozal dönemde olan kadınların, premenopozal dönemdeki kadınlara göre fiziksel ve psikosomatik alanlarda düşüş gösterdiğini ve bu farkın anlamlı olduğunu bildirdiler. 32 Birçok çalışmada, sonuçlarımızdan farklı olarak yaşam kalitesinin fiziksel fonksiyonlar ile ilişkili olduğu bildirilirken, bir çalışmada ağrı ile ilişkili olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…Premenopozal dönemdeki kadınların fiziksel fonksiyon skorları, perimenopozal dönemdeki kadınlarınkine göre oldukça yüksektir. 31 Mishra ve Kuh, yaşam kalitesi ile menopozal geçiş, sosyoekonomik faktörler, yaşam biçimi ve stres arasındaki ilişkiyi araştırdıkları çalışmalarında; en az 1 yıldır perimenopozal dönemde olan kadınların, premenopozal dönemdeki kadınlara göre fiziksel ve psikosomatik alanlarda düşüş gösterdiğini ve bu farkın anlamlı olduğunu bildirdiler. 32 Birçok çalışmada, sonuçlarımızdan farklı olarak yaşam kalitesinin fiziksel fonksiyonlar ile ilişkili olduğu bildirilirken, bir çalışmada ağrı ile ilişkili olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…Scores for each scale were later summed up and categorized as normal, mild, moderate, severe, and extremely severe. For depression, the total scoring was categorized as follows: normal (0-9), mild (10-13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (more than 28). For anxiety, the total scoring was categorized as normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (more than 20).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in the general population had shown that factors and predictors such as older age (12), depression (13), anxiety (14)(15)(16)(17), stress (18), chronic medical illness (19)(20)(21)(22)(23), poor financial status (24)(25)(26), low level of education (27,28), being single (29), family problem (30)(31)(32), and poor job satisfaction (33,34) may negatively affect QOL (35,36). However, there are limited data available pertaining to QOL among university staff.…”
Section: Introductionmentioning
confidence: 99%
“…In the current network environment, there are various systems, and a technology is needed to communicate in these heterogeneous systems. Web service is such a versatile "translator" [13]. e reason why Web services can communicate between heterogeneous systems is that Web services use XML (eXtensible Markup Language) as the carrier of information transmission.…”
Section: Web Services and System Architecture Design A Webmentioning
confidence: 99%